Music Review: U2, The Joshua Tree and Two Contrary States of Faith. The Joshua Tree 30th Anniversary Tour, Twickenham Stadium, UK: Sunday 9th July 2017 Music Review: U2, The Joshua Tree and Two Contrary States of Faith - Vaughan S Roberts (Journal for Religion, Film and Media, 2018)
A review and discussion of the 30th Anniversary Tour of The Joshua Tree in 2017 by Irish rock band U2, focussing on their second London show at Twickenham.